State capacity and welfare politics in India: implementing the Mahatma Gandhi National Rural Employment Guarantee Scheme in undivided Andhra Pradesh - Mukherji, Rahul; Zarhani, Seyed Hossein; Raju, K. (Indian journal of human development, 2018)
This article argues that the Indian state can develop the capacity to deliver economic rights in a citizen-friendly way, despite serious challenges posed by patronage politics and clientelism. Clientelistic politics reveals why the Indian state fails to deliver the basic rights such as the right to work, health and education. We argue that the ability of the state to deliver owes a lot to bureaucratic puzzling and political powering over developmental ideas in a path-dependent way. We combine powering and puzzling within the state to argue the case for how these ideas tip after they have gained a fair amount of traction within the state. We test the powering and puzzling leading to a tipping point model on the implementation of the Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) in undivided Andhra Pradesh (AP). How and why did undivided AP develop the capacity to make reach employment to the rural poor, when many other states failed to implement the right to work in India?
Gesehen am 26.11.2018